2016
DOI: 10.1016/j.radcr.2016.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous duodenal stenosis and duodenal web in a newborn

Abstract: Failure of duodenal recanalization results in a spectrum of proximal bowel obstruction from stenosis to atresia. Associations between congenital duodenal obstruction and other congenital anomalies have been well documented although the coincidence of duodenal stenosis and duodenal web is incredibly rare, posing a unique diagnostic challenge. We report a case of a full-term 4-day-old female child presented with forceful, bilious emesis and poor oral intake with decreased frequency of urination, and stooling who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 15 publications
2
8
0
Order By: Relevance
“…Other anomalies are anorectal malformations, esophageal atresia, cardiac defects, urinary and extremity anomalies (3)(4)(5)(6). However, these anomalies have no effect on survival (8). The most common additional anomaly in our study was Down Syndrome; no additional anomaly was found in any of the patients that we lost due to sepsis.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…Other anomalies are anorectal malformations, esophageal atresia, cardiac defects, urinary and extremity anomalies (3)(4)(5)(6). However, these anomalies have no effect on survival (8). The most common additional anomaly in our study was Down Syndrome; no additional anomaly was found in any of the patients that we lost due to sepsis.…”
Section: Discussionmentioning
confidence: 50%
“…The most common additional anomaly in our study was Down Syndrome; no additional anomaly was found in any of the patients that we lost due to sepsis. A mortality rate of 9% (6) in a study and 22.5% in another study were reported (8). The most common cause of mortality was sepsis and cardiac pathologies (6).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Intrinsic congenital duodenal obstruction refers to duodenal atresia, duodenal stenosis, and duodenal webs. The proposed etiology of intrinsic duodenal obstruction has been stated as failure of the duodenal lumen to recanalize during fetal development, which occurs at roughly 8-10 weeks in utero [4]. Duodenal atresia is the most common cause of congenital duodenal obstruction, with an incidence of roughly 1 in 10,000 live [5].…”
Section: Etiologymentioning
confidence: 99%
“…CT and MRI are usually not necessary and indicated only in cases where there is a diagnostic dilemma 12,13 (►Fig. 5 and 6).…”
Section: Duodenal Atresia/stenosis/web Spectrummentioning
confidence: 99%